Coupling to Tamm-plasmon-polaritons: dependence on structural parameters. (1st June 2018) - Kumari, Anupa; Kumar, Samir; Shukla, Mukesh Kumar; Kumar, Govind; Maji, Partha Sona; Vijaya, R; Das, Ritwick
Abstract: Tamm plasmon-polaritons (TPPs), formed at the interface of a plasmon-active metal and a distributed Bragg reflector (DBR), are characterized by sharp resonances in the reflection spectrum. The features of these sharp TPP resonances are primarily dictated by the structural parameters as well as by the nature of materials of the constituent DBR and metal. In the present investigation, we experimentally and theoretically analyze the role played by the DBR parameters and the metal layer thickness in determining the efficiency of TPP-mode excitation using plane waves. The findings reveal that the minimum in the reflection spectrum depicting the TPP resonance is strongly influenced by the thickness of plasmon-active metal film as well as the number of DBR unit cells. In fact, there exists an optimum combination of the geometrical parameters for achieving a maximum coupling to TPP modes. A brief theoretical analysis elucidating the underlying mechanism behind such observations is also presented so as to optimally design TPP-based architectures for different applications.